Succinate Promotes Phagocytosis of Monocytes/Macrophages in Teleost Fish - Yang, Dai-xiao; Yang, Hao; Cao, Yun-chao; Jiang, Ming; Zheng, Jun; Peng, Bo (Frontiers in Molecular Biosciences, 2021)
Development of immunity-based strategy to manage bacterial infection is urgently needed in aquaculture due to the widespread of antibiotic-resistant bacteria. Phagocytosis serves as the first line defense in innate immunity that engulfs bacteria and restricts their proliferations and invasions. However, the mechanism underlying the regulation of phagocytosis is not fully elucidated and the way to boost phagocytosis is not yet explored. In this manuscript, we profiled the metabolomes of monocytes/macrophages isolated from Nile tilapia, prior and after phagocytosis on Vibrio alginolyticus. Monocytes/macrophages showed a metabolic shift following phagocytosis. Interestingly, succinate was accumulated after phagocytosis and was identified as a crucial biomarker to distinguish before and after phagocytosis. Exogenous succinate increased the phagocytotic rate of monocytes/macrophages in a dose-dependent manner. This effect was dependent on the TCA cycle as the inhibitor of malonate that targets succinate dehydrogenase abrogated the effect. Meanwhile, exogenous succinate regulated the expression of genes associated with innate immune and phagocytosis. In addition, succinate-potentiated phagocytosis was applicable to both gram-negative and -positive cells, including V. alginolyticus, Edwardsiella tarda, Streptococcus agalactiae, and Streptococcus iniae. Our study shed light on the understanding of how modulation on host’s metabolism regulates immune response, and this can be a potent therapeutic approach to control bacterial infections in aquaculture.